Health Law and Stunting: How is the Government Handling in Eliminating Stunting? - Willya Achmad; Nunung Nurwati; Rd. Siti Sofro Sidiq (Government & Resilience, 2026)
Children's stunting is a significant public health issue that negatively impacts their growth and development. Dealing with stunting necessitates a comprehensive approach, including government efforts to address the issue via pertinent policies and laws. This study seeks to analyze the role of health law in efforts to eradicate stunting, with a particular focus on government action. The research method is normative legal research employing a qualitative approach by accumulating data through literature studies and analysis of documents pertaining to the treatment of stunting. Using an interpretive strategy, the collected data were analyzed to identify key issues regarding the function of health law in eradicating stunting. The results show that although Law No. 17 of 2023 provides a more integrative legal basis for the transformation of primary care, its effectiveness is still hampered by the less-than-imperative nature of the norms and the absence of firm sanctions for state officials who fail to meet nutrition service standards. Administrative barriers, such as weak cross-sectoral convergence, sectoral egos, and discrepancies in prevalence data, are key obstacles to implementation at the operational level. This study concludes that strengthening legal certainty through technical implementing regulations and simplifying budget bureaucracy is urgent. Its contribution lies in mapping regulatory gaps in the post-transition health law, while its limitations focus on normative analysis, which requires further empirical study in regions with low fiscal capacity.